Dynamic fire-atmosphere interaction in the 2020 Montana Bridger Foothills Wildfire as revealed by WRF-SFIRE simulations - Kevin K. W. Cheung; Jason Sharples; Dennis Del Favero; Carlos Tirado Cortes (npj Natural Hazards)
Abstract The Bridger Foothills (Montana, USA) wildfire event was notable due to its rapid escalation in fire activity, unique fire spread with respect to terrain and ambient wind direction, and endangerment to firefighters. To better understand the fire behaviour of this event, the WRF-SFIRE coupled atmosphere-fire model was used to conduct idealized and real-world simulations incorporating large eddy simulation. The model successfully simulated the lateral fire spread across the leeward slope, due to interaction between pyroconvection and eddy circulation over the slope. Both mechanisms of advection by terrain-modified local circulation and vorticity dynamics on the lee slope are found important to explain the event’s behavior. There are model discrepancies, which may be due to embers and spot fires not simulated in the model. The study demonstrated the critical role of high-resolution coupled modeling in supporting wildfire emergency responses and enhancing firefighter safety.